The stability of conditional cooperation: Egoism trumps reciprocity in social dilemmas - Luciano Andreozzi; Matteo Ploner; Ali Seyhun Saral (Max Planck Institute for Research on Collective Goods, 2019)
An often-replicated result in the experimental literature on social dilemmas is that a large share of subjects reveal conditionally cooperative preferences. Cooperation generated by this type of preferences is notoriously unstable, as individuals reduce their contributions to the public good in reaction to other subjects free-riding. This has led to the widely-shared conclusion that cooperation observed in experiments (and its collapse)is mostly driven by imperfect reciprocity. In this study, we explore the possibility that reciprocally cooperative preferences may themselves be unstable. We do so by observing the evolution of subjects' preferences in an anonymously repeated social dilemma. Our results show that a significant fraction of reciprocally cooperative subjects become selfish in the course of the experiment, while the reverse is rarely observed. We are thus driven to the conclusion that egoism is more resistant to exposure to social dilemmas than reciprocity.
hdl:21.11116/0000-0004-D561-E
Keywords: C72; C91; 330; reciprocity; conditional cooperation; strategy method